Economic valuation of structural capital through static and dynamic approaches: first evidence. (2016) - Lombardi, Rosa; Manfredi, Simone; Nappo, Fabio; Russo, Giuseppe
Under the current scenario, the economic assessment of intangible assets is a relevant issue in a company's decision-making processes. It follows that the determination of the real value of structural capital is the subject of academic debate because of the need to estimate this asset in a complete and comprehensive manner, including its static and dynamic evaluation. The economic value of structural capital is, in fact, used in company transactions, such as those involving mergers and acquisitions. The aim of our paper, therefore, is to analyse structural capital, illustrating the methods proposed in international literature. In particular, the purpose of this research is to demonstrate that the real options approach (ROA), using the Black and Scholes method, is useful in carrying out an economic assessment of dynamic intangible assets, such as patents and licences. Applying a qualitative and quantitative approach, the research findings of the paper are based on the application of Black and Scholes' method. Primary empirical evidence is derived from secondary sources and directed towards demonstrating the potential of the real options method in representing the dynamic value of structural capital.